STUDYING THE RELATIONSHIP MODEL BETWEEN VIRAL MARKETING AND e-WOM TOWARDS CUSTOMER LOYALTY LOCALOKA PLATFORM: A QUANTITATIVE APPROACH IN THE CREATIVE INDUSTRY - Kusuma, Rr. Chusnu Syarifa Diah; Farida, Farida; Seseli, Eka Merdekawati Imelda; Agwa, Terwase Richard (Sekolah Tinggi Ilmu Ekonomi Sultan Agung Pematangsiantar, 2025)
In today's digital era, marketing strategies that rely on the power of rapid message dissemination through social media and consumer networks play an important role in shaping customer perceptions and behaviour. This study examines the relationship model between viral marketing, electronic word-of-mouth (e-WOM), and customer trust towards customer loyalty on the Lokaloka platform, a digital marketplace operating in the creative industry sector. A quantitative approach was used in this study by distributing questionnaires to 200 respondents who are active users of the Lokaloka platform. Data analysis used the Structural Equation Modeling (SEM) method to test the direct and indirect relationships between variables. The results of the data analysis show that viral marketing, e-WOM, and customer trust have a significant influence on customer loyalty. The implications of this study indicate that creative industry platform managers such as Lokaloka need to strengthen community-based marketing strategies and content that is easily shared virally, as well as encourage positive interactions between users through e-WOM. In addition, building and maintaining customer trust is key to creating long-term loyalty. These findings are expected to contribute to developing a more effective digital marketing model in the Indonesian creative industry sector.